Implementasi Supervisi Akademik Mata Pelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama (SMP) Sekabupaten Kerinci - Saaduddin Saaduddin (Journal on Education, 2021)
This research is motivated by several fundamental issues related to the not yet optimal implementation of Islamic religious education learning supervision in Kerinci district junior high schools at this time and is a concern that needs to be addressed in the context of learning, because it can have an impact on low discipline and student learning outcomes. The teacher's performance itself is strongly influenced by factors such as the implementation of supervision. With this support, PBM of Islamic religious education at the junior high school level can slowly but surely be improved. The method used in this research is descriptive method. The sample used was 72 male and female Islamic religious education teachers or 22% of the total population. Gender is not separated because in essence these teachers have the same ability in terms of carrying out PBM activities in Islamic religious education at the junior high school level. The sampling technique used in this study was purposive sampling. The general conclusion from the results of this study is that the implementation of supervision in Islamic religious education subjects has not run optimally, this is evident from the percentage obtained at 45.27%. In terms of the implementation of supervision concerning aspects of learning management are in the sufficient category, namely 56.37%. The implementation of supervision concerning aspects of improving the teacher's academic ability in learning is in the sufficient category, namely 41%. Supervision involving aspects of professional development as Islamic religious education teachers by supervisors is in the less category, namely 35.97%.